The Prevalence of Headache and Associated Factors in Al-Kharj, Saudi Arabia: A Cross-Sectional Study - Almalki, Daifallah (Pain Res Manag, 2021)
BACKGROUND: Only few studies have investigated the prevalence and risk factors of headaches among the Saudi population. The study aimed to estimate the prevalence of headache and to explore its associated risk factors Al-Kharj, Saudi Arabia. METHODS: The multistage sampling technique was used to enroll 1200 population-based participants who were asked to complete a self-administered questionnaire about headaches, demographics, and several other parameters such as smoking status and different chronic and psychological illnesses. The chi-square test and multivariate logistic regression analysis were used to test the association. RESULTS: The overall prevalence of headaches in this study was 3%. The multiple logistic regression analysis showed that females were more likely to have headaches than males (odds ratio (OR) 0.735, 95% confidence interval (CI) = 0.612–1.341; P=0.024). Being a current smoker was also significantly associated with higher “odds” of having headache (OR = 1.319, 95% CI = 0.932–2.462; P=0.037). Participants who were overweight had a significantly higher risk of headache (OR = 1.631, 95% CI = 1.48–1.854; P=0.037). Nonmarried people were significantly more likely to have headache pain, compared to married individuals (OR = 0.875, 95% CI = 0.646–2.317; P=0.047). CONCLUSION: The prevalence of headaches was 3%, and four significant associated factors were identified: females, nonmarried, smoking, and overweight. The temporality of the relationship between these factors and headache cannot be confirmed in this cross-sectional study; so future longitudinal studies are needed to confirm these potential causal relationships.